ANALISIS PENGARUH UKURAN PERUSAHAAN, STRUKTUR KEPEMILIKAN, FAKTOR KOMITE AUDIT, RASIO PROFITABILITAS, DAN RASIO AKTIVITAS TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Vidya Nurpratiwi; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2014)
Going concern audit opinion is auditor’s modified opinion about the viability of a business. This study aims to provide empirical evidence on factors that affect the acceptance of going concern audit opinion. The variables used in this study are firm size, managerial ownership, institutional ownership, the activity of the audit committee, audit committee expertise, profitability ratio, and activity ratio.The population of this study is manufacturing companies listed in Indonesia Stock Exchange in 2010-2012. Purposive  judgement sampling technique was used to obtain the sample. The total sample of this study were 123 manufacturing companies. Data used in this study were audited financial statements and annual reports that were derived from the official website of the Indonesia Stock Exchange. Logistic regression was used to analyze the data.The results of this study showed that only firm size and institutional ownership have significant effect on the acceptance of going concern audit opinion, while managerial ownership, the activity of the audit committee, audit committee expertise, profitability ratio, and activity ratio do not have significant effect on the acceptance of going concern audit opinion.